Peran Inklusi Keuangan dan Financial Technology terhadap Kinerja UMKM Kuliner di Kota Mataram - Ahmad Geofani; Kayla Afifah; Bayu Kusuma (JURNAL ECONETICA: Jurnal Sosial, Ekonomi, dan Bisnis, 2025)
This study aims to analyze the role of financial inclusion and financial technology on the performance of culinary MSMEs in Mataram City. The background of the study is based on the importance of MSMEs as drivers of the regional economy and the persistent limitations in financial access and technology utilization among business actors. This study used a quantitative approach with an explanatory research method. Data were collected through questionnaires distributed to culinary MSMEs that met certain criteria, then analyzed using multiple linear regression to test the influence between variables. The results show that financial inclusion has a positive and significant effect on MSME performance. Access to formal financial services has been shown to improve business actors' ability to manage finances and expand their businesses. Financial technology also has a positive and significant effect on MSME performance, particularly in increasing transaction efficiency and accelerating operational processes. Simultaneously, these two variables contribute significantly to improving the performance of culinary MSMEs. These findings indicate that the integration of financial inclusion and the use of financial technology is a crucial factor in increasing the competitiveness of MSMEs in the digital era. This study implies that increasing financial access and technology adoption needs to be continuously encouraged through policy support and increased financial literacy. Thus, culinary MSMEs in Mataram City can develop more optimally and sustainably.